Effect of Chemical Preservatives on the Shelf Life of Bread at Various Temperatures - Lohano, Dileep Kumar; Sheikh, Saghir Ahmed; Shahnawaz, Muhammad (Pakistan Journal of Nutrition, 2010)
The study was conducted to evaluate the “effect of chemical preservatives on the shelf life of bread at various temperatures” at the Institute of Food Sciences and Technology, Sindh Agriculture University, Tandojam, in 2008. Two chemical preservatives i.e. calcium propionate (CP) and calcium lactate (CL) at (14±1), (22±1) and ambient temperature (32±2oC) were assessed for their effect on keeping quality of bread. The results conclude that effects of CP and CL at 14, 22 and (32±2oC) were equally significant at (p